Solve the system by substitution.

minus, 4, x, minus, y, equals, 1
−4x−y=
1
minus, 9, x, plus, 9, equals, y
−9x+9=
y

1 answer

To solve the system by substitution, we need to solve one equation for one variable and substitute that expression into the other equation.

Let's start by solving the second equation, "-9x + 9 = y," for y:
y = -9x + 9

Now we substitute this expression for y in the first equation, "-4x - y = 1":
-4x - (-9x + 9) = 1
-4x + 9x - 9 = 1
5x - 9 = 1

Adding 9 to both sides of the equation:
5x = 1 + 9
5x = 10

Dividing both sides of the equation by 5:
x = 10/5
x = 2

Now that we have found the value of x, we can substitute it back into the second equation to find y:
y = -9(2) + 9
y = -18 + 9
y = -9

Therefore, the solution to the system of equations is x = 2 and y = -9.